Personal values and its influence on ethical judgment of Malaysian future accountants / Suhaiza Ismail and Zuhudha Rasheed - Ismail, Suhaiza; Rasheed, Zuhudha (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The aim of this study was to investigate the influence of personal values on ethical judgement of future accountants in Malaysia. The study used a questionnaire survey and the respondents were final year undergraduate accounting students from three public universities in Malaysia. The questionnaire comprised of instruments about personal values and ethical judgment. A total of 205 usable responses were received. Descriptive statistics and multiple regression were performed to achieve the objectives. The findings revealed that self-transcendence and self-enhancement had significant influence on ethical judgment of future accountants in Malaysia. The remaining two personal values (conservation and openness to change) had no significant influence on ethical judgment. The study contributes to the empirical evidence on the types of personal values of future accountants and their influence on ethical judgment which is currently limited. To some extent, the findings are useful to enhance ethical judgment among future accountants in relation to their personal values, which will ultimately improve the credibility of the accounting profession.